4w-6(-4z+5w)-6z=

Simple and best practice solution for 4w-6(-4z+5w)-6z= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4w-6(-4z+5w)-6z= equation:


Simplifying
4w + -6(-4z + 5w) + -6z = 0

Reorder the terms:
4w + -6(5w + -4z) + -6z = 0
4w + (5w * -6 + -4z * -6) + -6z = 0
4w + (-30w + 24z) + -6z = 0

Combine like terms: 4w + -30w = -26w
-26w + 24z + -6z = 0

Combine like terms: 24z + -6z = 18z
-26w + 18z = 0

Solving
-26w + 18z = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-18z' to each side of the equation.
-26w + 18z + -18z = 0 + -18z

Combine like terms: 18z + -18z = 0
-26w + 0 = 0 + -18z
-26w = 0 + -18z
Remove the zero:
-26w = -18z

Divide each side by '-26'.
w = 0.6923076923z

Simplifying
w = 0.6923076923z

See similar equations:

| 4x+9=2+2(x+1)+2x+5 | | 22x=10 | | 7x+9-5x=11-2x-13 | | -4=1a+8-2a | | 7x+9-5x=11-2x-24 | | 6c-3=21 | | (11+5y)= | | -2+9(6x+4)=7-6(9x-3) | | 10(2x-11)=100x | | 5t+1-4t=-57 | | (11x+5y)= | | 1.5x=2.25y | | 1=1-6n-6 | | 0.3(18x+12)=-3x+40 | | X^2+11x=10x | | 2b+b+5b= | | -4(y+8)-4=51 | | 23=4t-7-1t | | -28x=14 | | 2.6=4t+3-0.4 | | 6x+2y+36=0 | | 2x(3x+xy)= | | 20=25-x | | 2(y-3)+4=6 | | 0.3-0.5x-2=21 | | 3x+2(x-4)+3=5x-5 | | 9(5x-6)=108x | | 2x(3x+5xy)= | | -27=7x-6 | | 80=47.6r+8 | | 12x-4=11x+19 | | n+11=-81 |

Equations solver categories